2012
DOI: 10.1117/1.jbo.17.8.081407
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative changes in human epithelial cancers and osteogenesis imperfecta disease detected using nonlinear multicontrast microscopy

Abstract: Abstract. We show that combined multimodal nonlinear optical (NLO) microscopies, including two-photon excitation fluorescence, second-harmonic generation (SHG), third harmonic generation, and fluorescence lifetime imaging microscopy (FLIM) can be used to detect morphological and metabolic changes associated with stroma and epithelial transformation during the progression of cancer and osteogenesis imperfecta (OI) disease. NLO microscopes provide complementary information about tissue microstructure, showing di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…TPEF is resulting from the nonlinear excitation of molecular fluorescence and that can visualize tissue architecture and cellular morphology. In addition to TPEF, SHG is well suited to observe collagen fibre structure in extracellular matrices that allows MPM to monitor changes in collagen composition during tumour development, whereas the changes were not obvious by standard histopathology (Adur et al ., ; Chen et al ., ). Due to the autofluorescence of properties in breast tissue, recent studies showed that the miniaturized MPM and multiphoton probe have potential ability for the noninvasive in vivo pathological diagnostic of breast tumour (Wu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…TPEF is resulting from the nonlinear excitation of molecular fluorescence and that can visualize tissue architecture and cellular morphology. In addition to TPEF, SHG is well suited to observe collagen fibre structure in extracellular matrices that allows MPM to monitor changes in collagen composition during tumour development, whereas the changes were not obvious by standard histopathology (Adur et al ., ; Chen et al ., ). Due to the autofluorescence of properties in breast tissue, recent studies showed that the miniaturized MPM and multiphoton probe have potential ability for the noninvasive in vivo pathological diagnostic of breast tumour (Wu et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques have already been widely used on ex-vivo tissue samples to perform optical biopsy for morphological characterizations [12], [13], [21]. However, there are only a few reports in the literature using SHG [22], [23] or TPEF+SHG [24] to analyze OI in skin samples.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the chemical specificity that characterizes fluorescence images, harmonic generation (SHG and THG) provides an imaging modality specific for structural configuration. In the study of cancer tumors, our experience with both techniques is that SHG is an excellent tool to observe collagen network of extracellular matrix, while THG allows to clearly display the nuclei, which are two key parameters for pathologists [4,[18][19][20]. In addition to harmonic generation microscopy, CARS microscopy is another 3D highresolution imaging approach that circumvents exogenous probes.…”
Section: Principles Of Nonlinear Microscopy Techniquesmentioning
confidence: 99%